AGE, SEX AND OBESITY HOSPITAL'S WORKERS IN BALIKPAPAN - Agustina, Elvi; Adrianto, Ratno; Azmiardi, Akhmad; Wirapuspita Wisnuwardani, Ratih (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Obesity remains a global health issue and a significant contributing factor to Non Communicate Disease (NCDs), so efforts to reduce the prevalence of obesity are very important. The impact of obesity on workers are very broad and includes aspects of physical, mental and productivity helath. The problem of study was the prevalence of obesity in RSUD dr. Kanujoso Djatiwibowo workers and its relationship with age and gender. Objective : This study aimed to determine the prevalence of obesity among workers of dr. Kanujoso Djatiwibowo hospital Balikpapan and in relationship with age and gender. Research Methods/ Implementation Methods : This research was cross sectional study conducted at Medical Check Up RSUD dr. Kanujoso Djatiwibowo Balikpapan in February 2023. A total 838 participants were selected by total sampling technique. Age and gender data were collected by medical record document and obesity data was calculated by measuring BMI and interpreted using WHO BMI Classification for Asia Pacific. The data were analyzed by Chi Square using SPSS. Results : Prevalence of obesity for workers in hospital ‘X” was 50,5%. Most was woman (51,8%) and age 41-50 years old (58,4%). There was a significant relationship between age and obesity (p value = 0,001), meanwhile gender was not statistically significant with obesity (p value = 0,353) Conclusion/Lesson Learned : More than half workers of hospital were obesity and age is statistically significant with obesity.